The legacy of Vaisnavism in colonial Bengal - Sardella, Ferdinando; Wong, Lucian (Routledge Hindu studies series, 2019)
Vaiṣṇavism in colonial Bengal : beyond the Hindu Renaissance / Lucian Wong, Ferdinando Sardella -- The afterlife of an avatāra in modern times / Varuni Bhatia -- Theorising Bengal Vaiṣṇavism : Bipin Chandra Pal and new perspectives on religious life and culture / Amiya P. Sen -- Vaiṣṇava institutional processes in colonial Bengal / Santanu Dey -- Baba Preraananda Bharati : his trajectory into and through Bengal Vaiṣṇavism to the West / Gerald T. Carney -- Claiming high ground : Gauḍīya missionising rhetoric on the adhikāra of worship / Kenneth Valpey -- Directions for future research on Vaiṣṇavism in colonial Bengal / Joseph T. O'Connell, Amiya P. Sen -- The power of the secret : the tantalising discourse of Vaiṣṇava Sahajiyā scholarship / Tony K. Stewart -- Sahajiya texts of Nadia : beyond reform and revival / Sukanya Sarbadhikary -- Love of woman : love of humankind? Interconnections between Bāul esoteric practice and social radicalism / Jeanne Openshaw -- Divine transgression : devotion and ethics in Bengali Vaiṣṇavism / Kiyokazu Okita -- Colonial morals, Vaiṣṇava quarrels : tracing the sources of nineteenth-century anti-Sahajiyā polemics / Lucian Wong.